Improvement in the flow of materials in the painting section of an industrial company - Ferreirinha, L. (2018)
This research was undertaken in the Painting section at the company Preh Portugal, which is currently increasing its capacity. The plastic components are painted and engraved, and then supplied to internal customers so that they can then be assembled on the final line. The main purpose of the study resides in analyzing the value flow. The methodology used consisted of the case study itself, in association with the use of lean tools. The objective was to reduce the changeovers generated by activities which, in the customer’s perspective, are of no added value. To this end, one studied the possibility of altering the configuration of the FIFO supermarket, as well as optimizing laser production in the section. The changes proposed resulted in gains of 74,02% and 74,4% regarding the distance of the routes covered by material and operators, respectively. Additional studies were carried out in the Painting section, more specifically in the new section of Painting. Here, one analyzed the layout projected by the company and subsequently carried out some changes which will enable gains of 48 and 43% in the distance of the routes covered by material and operators, respectively.